Sunflower seed meal as a substitute for soybean meal in broiler diets - Acda, Sonia P.; Almario, Alma L.; Luis, Edwin S. (1999)
One hundred eighty 12-day-old straight run broiler chicks were used to determine: 1) the effect of sunflower seed meal (SFM) as substitute for soybean meal on the performance of broilers, and 2) the economic benefits derived from using 0-30% SFM on a protein equivalent basis in broiler diets. All substitutions were in protein equivalent basis. Broilers fed diets with up to 30% sunflower seed meal performed as well as the broilers fed with corn-soya diet in terms of average body weights, body weight gain, feed consumption, and feed efficiency. Dressing percentage, lean fat bone yield and sensory scores on flavor, color, tenderness, juiciness, off-flavor and general acceptability were likewise not significantly different. In addition, higher income over feed and chick cost was generated from broilers fed diets with SFM relative to those fed corn-soya diet. Thus, SFM can be used as a substitute for soybean meal up to 30% protein equivalent without significantly affecting the performance and carcass quality of broilers.
Keywords: Broilers (Poultry) -- Feeding and feeds; Seeds; Soybean; Sunflowers